A Pilot Randomized Controlled Trial of Acceptance and Commitment Therapy Guided Self-Help for Overweight and Obese Adults High in Weight Self-Stigma. Issue 1 (January 2022) - Potts, Sarah; Krafft, Jennifer; Levin, Michael E.
Weight self-stigma, in which individuals internalize stigmatizing messages about weight, is a prevalent problem that contributes to poor quality of life and health. This pilot randomized controlled trial evaluated acceptance and commitment therapy (ACT) guided self-help using The Diet Trap for 55 overweight/obese adults high in weight self-stigma. Participants were randomized to the ACT self-help book plus phone coaching (GSH-P; n  = 17), self-help book plus email prompts only (GSH-E; n  = 20), or a waitlist condition ( n  = 18), with online self-report assessments at baseline and posttreatment (8 weeks later). Participants reported high satisfaction ratings and engagement with the ACT self-help book, with no differences between GSH-P and GSH-E. Both GSH-P and GSH-E improved weight self-stigma relative to waitlist with large effect sizes. There were mixed findings for health outcomes. The GSH-P condition improved more on healthy eating behaviors and general physical activity, but neither ACT condition improved more than waitlist on self-reported body mass index, emotional eating, and a second measure of physical activity. Results suggest an ACT self-help book with email prompts can reduce weight self-stigma and potentially improve some health behavior outcomes. Phone coaching may provide additional benefits for generalizing ACT to diet and physical activity.